Study of mechanical and water absorption properties of bio-composite thin film from waste banana peel - Chee Wing Tung (2017)
The purpose of this study was to fabricate bio-composite from waste banana peel with 0 %, 5 % and 10 % of eggshell filler. Banana peel fibre acts as matrix while eggshell acts as filler. After boiling dry banana peel, it was blended with eggshell filler and glycerol which acts as plasticizer. The mixture was poured on silkscreen and dried in oven. Hand lay-up process was used to laminate the biocomposite with epoxy. The procedures were repeated by using different ratio of banana peel and eggshell. The effect of different ratios of waste banana peel and eggshell filler in bio-composite thin film was determined. The mechanical properties of the bio-composite were determined by using tensile test and tear resistance test. The tensile strength and Young’s modulus increased while the percent elongation decreased as the eggshell filler contents increased. Sample with 10 % of eggshell filler showed the highest tensile strength. This proved that eggshell was an effective filler in improving strength of the bio-composite. On the other hand, the tear strength decreased with the incorporation of eggshell filler. The highest tear strength was observed for the sample with 0 % of eggshell. The observation for fracture behaviour of the samples was carried out by using scanning electron microscope. The water absorption properties of the bio-composite were determined by using water absorption test. Sample with 10 % of eggshell filler absorbed the highest amount of water. The percentage of water absorption increased as the filler content increased.